Lacustrine paleoshoreline determination under established sequence stratigraphic framework and its controls on sand bodies and hydrocarbon accumulations. (December 2019) - Fu, Sheng; Liu, Zhen; Guo, Yan-ru; Ge, Jia-wang; Xu, Xiao-ming
Abstract: The lacustrine palaeoshoreline is the intersection between lake level and ancient land in geological time, and it marks the boundary between onshore deposits and subaqueous deposits. Identifying lacustrine paleoshorelines is the process of reconstructing past depositional environments. The study establishes the sequence stratigraphic framework of the Ordos Yanchang Formation based on a comprehensive analysis of seismic and well log data. The hierarchical lithological cycles is determined through Fourier transform and band-pass filtering analysis of Gramma Ray data. Subsequently, the lacustrine paleoshoreline is determined using the shoreline hierarchical control method under the established sequence stratigraphic framework, with additional evidence from cores, well logs and cutting and seismic sections. Lacustrine paleoshorelines has controlling effects on the sand bodies and hydrocarbon accumulations. For one thing, different types of paleoshoreline control the genesis of sand bodies, and the location of paleoshoreline in sag basin controls sand-body distribution. Furthermore, the migration of lacustrine paleoshoreline in sag basin indicates stacking patterns of sand bodies, and hydrocarbon accumulations. Highlights: The sequence stratigraphic framework establishment of the Yanchang Formation in Ordos Basin. The hierarchy of lithological cycles determined through Fourier transform and band-pass filtering of Gramma Ray data. Lacustrine paleoshoreline determination using shoreline hierarchical control method with other sedimentological evidences. A key control of lacustrine paleo-shoreline on sand bodies and hydrocarbon accumulations in sag basins.